Digital Transformation of Village Administration: Development of Integrated Population and Social Assistance Information System - Yera Wahda Wahdi; Muhamad Safi’i; Novi Hendri Adi; Atman Lucky Fernandes; Riski Wulandari Hutagaol (Ikatan Ahli Informatika Indonesia, 2025)
The management of population data in rural areas creates significant barriers to the effective distribution of social assistance. This research aims to develop and validate an integrated web-based information system that combines population administration with a multi-level social assistance verification mechanism to improve targeting accuracy and administrative efficiency in Ngal Village, Karimun Regency, Riau. The system was developed using the Waterfall Method through five systematic stages: requirements analysis, system design using UML modeling, web-based implementation, Black Box testing, and instrument validation. The research results show an integrated system capable of managing population data and social assistance eligibility criteria in real-time. Black Box testing shows that all system functions were successfully executed with a 100% success rate. Validity analysis using Aiken-V on 32 respondents showed very high values across four dimensions: System Function (0.98), Content Suitability (0.98), Ease of Use (0.95), and Interface Design (0.92). System implementation successfully reduced and eliminated data duplication errors and improved administrative efficiency. This research fills a critical gap in the village information systems literature by providing an integrated solution that addresses population administration and social assistance distribution. The validated system demonstrates effectiveness in an island context with limited connectivity, offering a replicable model for digital transformation in rural governance.